2004
DOI: 10.1055/s-2004-821176
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pathogen Resistance in Barley by Abiotic Stress

Abstract: Enhanced resistance of barley (Hordeum vulgare L. cv. Ingrid) against barley powdery mildew (Blumeria graminis f. sp. hordei race A6) was induced by abiotic stress in a concentration-dependent manner. The papilla-mediated resistance was not only induced by osmotic stress, but also by proton stress. Resistance was directly correlated with increasing concentrations of various salts in the nutrient solution. Resistance induced by proton stress also depended on the stress intensity. Resistance induction occurred e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…In addition, Mohr and Cahill (2003) reported that treatment of Arabidopsis with ABA conferred partial loss of resistance against an avirulent isolate of P. syringae pv tomato. Contrary to these reports, Wiese et al (2004) recently described a positive role for ABA in pathogen resistance. The authors showed that treatment of barley with ABA primed for papillae-mediated resistance against powdery mildew fungus (Blumeria graminis f sp hordei ).…”
Section: Aba Regulates Baba-induced Protection Against Salt Stress Anmentioning
confidence: 67%
“…In addition, Mohr and Cahill (2003) reported that treatment of Arabidopsis with ABA conferred partial loss of resistance against an avirulent isolate of P. syringae pv tomato. Contrary to these reports, Wiese et al (2004) recently described a positive role for ABA in pathogen resistance. The authors showed that treatment of barley with ABA primed for papillae-mediated resistance against powdery mildew fungus (Blumeria graminis f sp hordei ).…”
Section: Aba Regulates Baba-induced Protection Against Salt Stress Anmentioning
confidence: 67%
“…For example, both salt stress and exogenous ABA enhance the resistance of barley (Hordeum vulgare) to the biotrophic powdery mildew fungus Blumeria graminis (Wiese et al, 2004). Likewise, ABA application enhances resistance of Arabidopsis to the oomycete Pythium irregulare, while ABA-deficient and ABA-insensitive mutants are more susceptible (Adie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of barley roots with ABA activated resistance in response to Blumeria graminis f. sp. hordei, and the pustule number was reduced by more than 50% [39]. Furthermore, the exogenous application of ABA-induced resistance of Arabidopsis against Alternaria brassicicola and Plectosphaerella cucumerina in wild-type plants [36].…”
Section: Introductionmentioning
confidence: 99%